Primary squamous cell carcinoma of renal parenchyma: A case report and literature review - Liang, Ke; Yuan, Yichu; Lv, Bodong; Ke, Zunjin (Frontiers in Oncology, 2023)
Primary renal parenchymal squamous cell carcinoma (SCC) is an extremely rare tumor that is difficult to diagnose by hematology and imaging studies, and is often diagnosed later than other primary renal cancers. This article reports a case of a patient who was admitted to the hospital with a diagnosis of renal cyst in the outpatient department. Further renal enhanced MR was considered to be cystic renal carcinoma of the right kidney. The contraindication was excluded. Robot-assisted partial right nephrectomy under general anesthesia was performed. The postoperative pathology showed that the right kidney was elevated. Differentiated squamous cell carcinoma with cystic degeneration. During the 5-month follow-up, the patient recovered well, and there was no treatment metastasis or recurrence.